If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13x+6=7x+92
We move all terms to the left:
13x+6-(7x+92)=0
We get rid of parentheses
13x-7x-92+6=0
We add all the numbers together, and all the variables
6x-86=0
We move all terms containing x to the left, all other terms to the right
6x=86
x=86/6
x=14+1/3
| 7x/3+2=-2 | | 60+123=4c | | x+(x+489)+(x+1372)=6502 | | 1.6·y=9 | | 8/7x-11=10/7x+20 | | 4(3-x)+2x=8 | | 0=6+24t-16t^2 | | 3q+2=2 | | 44n²-4n-90=0 | | 0=2500-22x | | 6(x-5)=-2(x+43 | | x2−3x−13.75=0 | | 3r= | | 4x-2+2x=8x-10 | | 16=x^2-2x-8 | | 0=-16t2+80t | | -0.5x+1=2 | | 2x+3(1)=4 | | 2x+3x1=4 | | 3000+x-2000=1500+1000 | | (5i)(3i)=0 | | Y+45/5+y-11/8=6 | | 14/17x=70 | | (x-7)^2-20=0 | | 5+8x=-19 | | 10x^2+209x+9=0 | | 3x+3=148 | | w-35/6=21/3 | | v^2-3v=-28 | | 10x^2+389x+49=0 | | x-5÷8= | | 3x+6.66=20 |